2012
DOI: 10.1016/j.geoforum.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Sibling caringscapes: Time–space practices of caring within youth-headed households in Tanzania and Uganda

Abstract: a b s t r a c tThis paper investigates the time-space practices of young people caring for their siblings in youthheaded households affected by AIDS in Tanzania and Uganda. Based on qualitative exploratory research with young people heading households, their siblings, NGO workers and community members, the article develops the notion of sibling 'caringscapes' to analyse young people's everyday practices and caring pathways through time and space. Participatory time-use data reveals that older siblings of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 43 publications
1
61
0
1
Order By: Relevance
“…Sibling birth order, age and gender were significant factors in determining the position, authority and roles accorded to different siblings within the household following parental death, confirming research findings from other contexts in the global South (Evans 2012;Punch 2001). The eldest son was expected to inherit his father's and paternal uncles' land, livestock and other assets to manage these, provide for the household and become responsible for all decisions about household expenses following the death of the male head of household, as seen here in the example of Issa.…”
Section: Vital Conjunctures: Emotional Responses To Parental Deathsupporting
confidence: 80%
See 1 more Smart Citation
“…Sibling birth order, age and gender were significant factors in determining the position, authority and roles accorded to different siblings within the household following parental death, confirming research findings from other contexts in the global South (Evans 2012;Punch 2001). The eldest son was expected to inherit his father's and paternal uncles' land, livestock and other assets to manage these, provide for the household and become responsible for all decisions about household expenses following the death of the male head of household, as seen here in the example of Issa.…”
Section: Vital Conjunctures: Emotional Responses To Parental Deathsupporting
confidence: 80%
“…According to Islamic law, daughters are expected to receive half of the share of inherited assets that their brothers receive, but the research found that this did not usually include land. Furthermore, in one of the research locations, some agricultural land and rice paddies were regarded as belonging to the maternal lineage (Evans 2012).…”
Section: Introduction: Youth Life Transitions and Parental Deathmentioning
confidence: 99%
“…This is approached less from the perspective of 'nudge' behavioural economics and the 'psychological state' (Jones, Pykett and Whitehead 2013), and more by drawing on Bondi's (2008) discussion of the relational theory of practice which emphasises that the interpersonal relationships and dynamics between service providers and their clients are the ultimate mediums of policy delivery and not just contingencies (see also Hunter 2012). Importantly, and relating to wider debates about young people's agency in the context of care and intergenerational relations within and outside the neoliberal mainstreams of both the Global North and South (Evans 2012, Punch and Sugden 2013, we focus on 2 young people not only as 'recipients' of care (Wiles 2011), but also as active participants in the relational and situated practices such as mentoring and, consequently, policy delivery (Dickens and Lonie 2013). Second, the paper considers an expanded notion of relational practice in the emerging contexts of social policy and care economies.…”
Section: Introductionmentioning
confidence: 99%
“…In view of adult–child power relations and generational hierarchies, I was aware that young people might find it difficult to express their views in a workshop dominated by adults. I also recognised that young people may not have time to participate in another workshop, given the time scarcity they faced in juggling substantial care work with school, agricultural labour and other livelihood activities (Evans ). Showing the children's video‐dramas/song was intended to be a way of enabling their priorities to be heard without needing them to be physically present.…”
Section: Ethical Dilemmas Raised By Participatory Disseminationmentioning
confidence: 99%
“…This reveals the potential emotional conflicts and paradoxes of action‐oriented research; the process enabled the identification of participants’ needs for care and support, yet my own and other stakeholders’ competence (Tronto ) to provide the care needed was compromised by caring responsibilities to ‘proximate’ others, limited time, insufficient resources and wider structural inequalities which determine the care resources available to child‐ and youth‐headed households at local level (Evans ).…”
Section: Ethical Dilemmas Raised By Participatory Disseminationmentioning
confidence: 99%